The effectiveness of Benson's relaxation technique on pain and perceived stress among patients undergoing hemodialysis: a double-blind, cluster-randomized, active control clinical trial - Abu Maloh, Haya Ibrahim Ali; Soh, Kim Lam; Chong, Seng Choi; Ismail, Siti Irma Fadhilah; Soh, Kim Geok; Abu Maloh, Dima Ibrahim; Al Yateem, Nabeel; Aburuz, Mohannad Eid (SAGE Publications, 2023)
Benson’s relaxation affects many symptoms among hemodialysis patients. A cluster-randomized active control clinical trial with three repeated measures; pre, 1-week, and 1-month post-intervention sought to evaluate the effectiveness of Benson’s Relaxation on pain and perceived stress (P&PS) among hemodialysis patients. Two governmental hospitals were randomly assigned to intervention and control. Thirty-six participants were randomly selected; 18 were intervention, and 18 were controlled. The intervention group performed Benson’s Relaxation twice a day for 10 minutes for 8 weeks after a training session. The control group received an educational session about Progressive Relaxation. Findings revealed a statistically significant reduction in the PSS-10 and PRI scores between pre-intervention and 1 month after-intervention (p < .001) and at 1 week after intervention and 1 month after-intervention (p < .001). A non-statistically significant reduction between pre-intervention and 1 week after-intervention (p > .05). Benson’s Relaxation significantly relieved P&PS among hemodialysis patients but not after only 1 week of practicing.